Free and forced vibration analysis of 3D printed bioinspired sandwich beam using HSDT: Numerical and experimental study. Issue 6 (12th April 2022) - Gunasegeran, Muthukumaran; Edwin Sudhagar, P.
Abstract: Sandwich structures are used in aircraft, automobiles, and naval industries. The sandwich cores have a substantial impact on their structural behavior. The core design is a significant influencing factor in sandwich structures, and the core selection is even more critical. This study investigates the free and forced vibration analysis of bioinspired sandwich beams. The bioinspired PLA core is 3D printed by fused deposition modeling, and GFRP skin is fabricated using hand layup techniques. The complex shear modulus of the bioinspired core and the elastic modulus of the skin is evaluated using the alternative dynamic method and ASTM E1876, respectively. Among various bioinspired composite sandwich beam configurations, BIM02 produces the highest stiffness, followed by BIM01, BIM04, and BIM03 because of the strain energy distribution. Pattern arrangement of the core in the bioinspired sandwich beam has a significant difference in the natural frequencies. Further, a parametric study of the sandwich beam for four different 3D printed bioinspired PLA cores and ply configuration of the GFRP skin using Higher Order Shear Deformation Theory (HSDT). Abstract :